The use of Ursodesoxicolic Acid in Prevention of Collelitiase After Bariatric Surgery: A Systematic Review of Literature - Magalhães, Bráulio Filgueira; Leite, Pedro de Sousa; Moreira, Gabriella Rocha; Araújo, Yanny Brena Alencar; Cruz, Natália Mendes; Rolim, Francisco Felippe de Araújo (Amadeus International Multidisciplinary Journal, 2019)
Morbid obesity is considered a serious public health problem generating high human and financial costs. The situation that promotes the highest morbidity after bariatric surgery is the development of cholelithiasis, especially in the first 6 months. Given this process, ursodeoxycholic acid is increasingly being used in the postoperative period due to a reduction in the rate of cholelithiasis. However, there are discussions of which prophylactic method to use. In this context, a systematic review was performed to evaluate the efficacy and use of ursodeoxycholic acid in preventing cholelithiasis after bariatric surgery. After methodological analysis, 6 articles were selected. These studies suggest that administration of 500 to 1000 mg of UDCA for a period of 6 months, depending on the technique used, is significantly associated with decreased incidence of cholelithiasis, with good adherence, cost-effectiveness and few side effects. Keywords: Ursodeoxycholic Acid, Cholelithiasis, Bariatric Surgery.